Comparative physiological and transcriptomic analyses provide insights into fruit softening in Chinese cherry [Cerasus pseudocerasus (Lindl.) G.Don] - Wang, Yan; Ma, Lan; Ma, Yan; Tian, Tai; Zhang, Jing; Wang, Hao; Liu, Zhenshan; Chen, Qing; He, Wen; Lin, Yuanxiu; Zhang, Yunting; Li, Mengyao; et al. (Frontiers in Plant Science, 2023)
Fruit softening is a complex, genetically programmed and environmentally regulated process, which undergoes biochemical and physiological changes during fruit development. The molecular mechanisms that determine these changes in Chinese cherry [Cerasus peseudocerasus (Lindl.) G.Don] fruits are still unknown. In the present study, fruits of hard-fleshed ‘Hongfei’ and soft-fleshed ‘Pengzhoubai’ varieties of Chinese cherry were selected to illustrate the fruit softening at different developmental stages. We analyzed physiological characteristics and transcriptome profiles to identify key cell wall components and candidate genes related to fruit softening and construct the co-expression networks. The dynamic changes of cell wall components (cellulose, hemicellulose, pectin, and lignin), the degrading enzyme activities, and the microstructure were closely related to the fruit firmness during fruit softening. A total of 6,757 and 3,998 differentially expressed genes (DEGs) were screened between stages and varieties, respectively. Comprehensive functional enrichment analysis supported that cell wall metabolism and plant hormone signal transduction pathways were involved in fruit softening. The majority of structural genes were significantly increased with fruit ripening in both varieties, but mainly down-regulated in Hongfei fruits compared with Pengzhoubai, especially DEGs related to cellulose and hemicellulose metabolism. The expression levels of genes involving lignin biosynthesis were decreased with fruit ripening, while mainly up-regulated in Hongfei fruits at red stage. These obvious differences might delay the cell all degrading and loosening, and enhance the cell wall stiffing in Hongfei fruits, which maintained a higher level of fruit firmness than Pengzhoubai. Co-expressed network analysis showed that the key structural genes were correlated with plant hormone signal genes (such as abscisic acid, auxin, and jasmonic acid) and transcription factors (MADS, bHLH, MYB, ERF, NAC, and WRKY). The RNA-seq results were supported using RT-qPCR by 25 selected DEGs that involved in cell wall metabolism, hormone signal pathways and TF genes. These results provide important basis for the molecular mechanism of fruit softening in Chinese cherry.